EFEK INOVASI TERHADAP KINERJA USAHA KECIL DAN MENENGAH - I Nengah Aristana; Made Christin Dwitrayani; Ni Made Ernila Junipisa; I Ketut Eli Sumerta (Universitas Triatma Mulya, 2022)
The development of the economy in Indonesia cannot be separated from the participation of small and medium enterprises (SMEs), while the form of interaction between SMEs is seen by their participation as providers of employment and their contribution to gross domestic product. The purpose of this study is to analyze the effect of product innovation, process innovation, and management innovation on performance. Measuring the effect of innovation on performance and which indicator variables have an effect on performance. This study used a quantitative approach by involving 262 SMEs as a sample. The multiple linear regression analysis techniques with the SPSS 21 program were used to answer the hypothesis. The results obtained are product innovation that has a significant positive effect on performance, process innovation has a positive and insignificant effect on performance and management innovation has a significant negative effect on performance. The magnitude of the influence of the variable product innovation, innovation process, and management innovation on performance is still in a low category of 5.6% and the innovation variable has a dominant effect on the performance of SMEs.